Applications and perspectives of gas analysis based on sonar instrumentation. (March 2019) - Rossi, C.; Battistin, M.; Bortolin, C.; Crespo-Lopez, O.; Deterre, C.; Doubek, M.; Hallewell, G.; Katunin, S.; Nagai, K.; Pearson, B.; Robinson, D.; Rozanov, A.; et al.
Highlights: Ultrasonic instruments allow real time binary gas mixture monitoring. High precision is demonstrated (>10 –4 M) depending on molecular weight difference. They can be used in binary gas analysis with known concentration of third-party gases. Other applications of these instruments are foreseen. Abstract: We have developed ultrasonic instrumentation to simultaneously monitor flow and composition in a variety of gas mixtures. Flow and mixture composition are respectively derived from measurements of the difference and average of sound transit times in two opposite directions in a flowing process gas blend. Gas composition is then determined from an automated comparison of the measured sound velocities with a velocity/composition database. Continuous, real-time precision measurements of binary gas mixtures are required in many applications. While the most natural application of this instrumentation is in the analysis of such mixtures, analysis of mixtures with additional components is also possible, as discussed in this paper. In the ATLAS experiment at CERN, several instruments are presently used in the Detector Control System. Three instruments monitor octafluoropropane (C3 F8, R218) and carbon dioxide (CO2, R744) coolant leaks into the nitrogen-purged envelopes surrounding elements of the inner silicon tracker. Precision in molar concentration of better than 2.10 −5 is routinely seen in mixtures of C3 F8 in nitrogen in the presence of known concentrations of the third party gas CO2 . Two further instruments are used to monitor the new 60 kW thermosiphon C3 F8 evaporative coolant recirculator which exploits the 90 m depth of the ATLAS pit to circulate coolant without the need for pumps or compressors in the primary loop. These instruments are used to verify the absence of air leaks in the thermosiphon cooling circuit and to measure the vapour-phase coolant flow in real-time. This instrumentation is also used to measure zeotropic fluorocarbon blends containing C3 F8 and up to 25% hexafluoroethane (C2 F6, R116), achieving a precision around 0.16% in the range 0–25% C2 F6 . We also report on measurements of heat transfer coefficient in these blends: our experimental data were compared to several empirical correlations, with typical differences less than 10%. This analysis technique, targeting binary pairs of gases of dissimilar molecular weight, is particularly promising for mixtures of anesthetic gases, including in the developing area of anesthesia using xenon. The instrument and its various applications will be discussed.